The effect of systematic couple group therapy on families with depressed juveniles: a pilot trial - Meng, Tian-Jiao; Qian, Ying; Wang, Yu-Lu; Gao, Bing-Ling; Liu, Jia-Jia; Yue, Jing-Li; Tang, Deng-Hua (Frontiers in Psychiatry, 2024)
Background. Depression is a primary cause of illness and disability among teenagers, however, the incidence of depression and the number of untreated young people has increased in recent years. Effective intervention for those youths could decrease the illness burden and suicidal or self-harm risk during preadolescence and adolescence.Objective. To verify the short efficacy of the systematic couple group therapy (SCGT) on youth's depression changes and family with depressed adolescents.Methods. The study was a self-control trial, only within-group changes were evaluated.Participants were couples with a depressed child who was resistant to psychotherapy, recruited non-randomly through convenient sampling. Paired-sample T test and Wilcoxon signed-rank test were used to compare differences before and after interventions. The effect sizes were also estimated by Cohen's d. Spearman correlation analysis was used to examine associations between changes.Results. A downward trend was seen in depressive symptoms after treatment, and the Cohen's d was 0.33 (p=0.258). The adolescents perceived less interparental conflicts, and the effect sizes were medium for the perceived conflict frequency (0.66, p=0.043), the conflict intensity (0.73, p=0.028), the conflict solutions (0.75, p=0.025), the coping efficacy (0.68, p=0.038) and the perceived threat (0.57, p=0.072). As for parents, the global communication quality, constructive communication patterns and subjective marital satisfaction significantly improved after interventions, with large effect sizes (1.11, 0.85 and 1.03, respectively; all p=0.000). Other destructive communication patterns such as demand/withdraw (p=0.003) and mutual avoidance (p=0.018), and communication strategies like verbal aggression (p=0.012), stonewalling (p=0.002), avoidance-capitulation (p=0.036) and child involvement (p=0.001) also reduced, with medium effect sizes (0.69, 0.52, 0.55, 0.71, 0.46 and 0.79, respectively). Meanwhile, the associations between depression changes and changes of interparental conflicts (p=0.000) and marital satisfaction (p=0.001) were significant.Conclusions and clinical relevance. The SCGT offers a possibility for the treatment of families with depressed children lack of seeking treatment. Helping parents improve communication and marital quality might have benefit on children's depressive symptoms in their families.